2008
DOI: 10.1111/j.1750-3639.2008.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin and Melanin‐Concentrating Hormone in Patients with Huntington Disease

Abstract: To evaluate whether hypocretin-1 (orexin-A) and melanin-concentrating hormone (MCH) neurotransmission are affected in patients with Huntington disease (HD), we immunohistochemically stained hypocretin and MCH neurons and estimated their total numbers in the lateral hypothalamus of both HD patients and matched controls. In addition, hypocretin-1 levels were determined in prefrontal cortical tissue and post-mortem ventricular cerebrospinal fluid (CSF) using a radioimmunoassay. The total number of hypocretin-1 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 41 publications
6
86
0
2
Order By: Relevance
“…При таких заболеваниях, как болезнь Паркинсона [58,59], хорея Гантингтона [60], детектировалось значительное снижение ко-личества гипоталамических орексин-содержащих нейронов (у более 50% популяции), но уровень орексина А в спинномозговой жидкости часто оставался в пределах нормы [61].…”
Section: Introductionunclassified
“…При таких заболеваниях, как болезнь Паркинсона [58,59], хорея Гантингтона [60], детектировалось значительное снижение ко-личества гипоталамических орексин-содержащих нейронов (у более 50% популяции), но уровень орексина А в спинномозговой жидкости часто оставался в пределах нормы [61].…”
Section: Introductionunclassified
“…The finding of reduced numbers of orexin neurons in the rodent models (10-70%) have now been established in human HD where there is a decrease of around 30% of orexin-positive neurons in the hypothalamus [84,89] . Hypothalamic atrophy, similar to that detected in R6/2 mice, has been reported in two clinical studies using voxel-based morphometry of magnetic resonance images from early HD patients [90,91] , but detailed neuropathological studies examining the survival of distinct neuronal subtypes in the whole hypothalamic region in human HD have yet to be performed.…”
Section: Hypothalamic Changes In Hdmentioning
confidence: 99%
“…CART = Cocaine-and amphetamine-regulated transcript; POMC = proopiomelanocortin; MCH = melanin-concentrating hormone; ACTH = adrenocorticotropic hormone. [82,83] atrophy [90,91] Orexin loss of orexin: R6/2, YAC128 [84,86] loss of orexin [84,89] HPA axis upregulation: R6/2 [96] upregulation [96,102,104] Testosterone increased plasma levels: R6/2 [106] increased plasma levels [108] Insulin insulin resistance: R6/2, N171-82Q [96,115] insulin resistance [125] Leptin decreased plasma levels: R6/2, N171-82Q, CAG140 [77,115] decreased plasma levels [116] …”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…AD is a neurodegenerative disorder that affects multiple brain areas as well as types of neurons and most likely includes the primary sleep-regulating systems. As the hypocretin system is affected in various neurodegenerative diseases such as Parkinson's and Huntington's disease [8,9,10], we hypothesized that the neurodegenerative process in AD might also affect the hypocretin system, which could contribute to the sleep disturbances of AD patients. The observation of Friedman et al [11], who have shown an inverse relation between lumbar CSF hypocretin-1 concentration and the amount of daytime naps of AD patients, supports this possibility.…”
Section: Introductionmentioning
confidence: 99%